Comparison of the gradient diffusion technique for fluconazole and voriconazole with the VITEK 2 yeast susceptibility system for clinical breakpoints of candida tropicalis isolated from clinical samples. - Rajpal, Kamlesh; Kumari, Namrata; Kumar, Shailesh; Kumar, Rakesh; Saurabh, Kumar; Kumar, Randhir (Student’s Journal of Health Research Africa, 2025)
Background Modern health care advances in immunosuppressive therapy, particularly related to bone marrow transplantation, and increasing utilization of implantable devices have contributed to the rise of invasive Candida infections in recent decades. Objectives: An automated method based on the broth microdilution MIC technique was used to evaluate the susceptibility of fluconazole and voriconazole with that of the Gradient diffusion technique using brain heart infusion (BHI) agar. Additionally, to identify a low-cost, quick, accurate, and simple way to test for antifungal sensitivity. Materials and Methods Over a year, an observational study was conducted from November 2023 to October 2024. The study was carried out at the Department of Microbiology at the Indira Gandhi Institute of Medical Sciences (IGIMS), Patna, Bihar, India. The study included 120 participants in total. Results Out of 120 isolates of Candida species, a total of 40 isolates were found to be of Candida tropicalis. Most of the isolates were confirmed in blood samples 24 (60%), followed by deep aspirated pus 06 (15%), pleural fluid 05 (12.5%), CSF 03 (7.5%), and peritoneal fluid 02 (5%). Candida tropicalis isolates were sensitive to fluconazole in 37 (92.5%) of the species as well as to voriconazole in 39 (97.5%) of the species through Vitek 2 tests. Conclusion A standardized automated test for antifungal susceptibility, the AST-YS08Vitek 2 card system (bioMérieux), was shown to be dependable and produced findings that were comparable to the E test; as a result, it may be used in place of the E test. Recommendations Nevertheless, additional research is required to assess the VITEK 2 method’s capacity to detect resistant isolates. Retesting of any resistant isolates generating inconsistent findings will be necessary to resolve this problem.